Visceral Therapy and Physical Activity for Selected Dysfunctions, with Particular Emphasis on Locomotive Organ Pain in Pregnant Women-Importance of Reducing Oxidative Stress - Małgorzata Wójcik; Grażyna Jarząbek-Bielecka; Piotr Merks; Dawid Luwański; Katarzyna Plagens-Rotman; Magdalena Pisarska-Krawczyk; Małgorzata Mizgier; Witold Kędzia (MDPI AG, 2022)
Movement is a physiological phenomenon and a fundamental aspect of the living human body in a global context (e.g., musculoskeletal system function) and local one (e.g., visceral system function). The local activity of the body is expressed in the rhythm of pulsations, peristalsis and vibrations. Visceral therapy supports movement, articulation and tissue rhythm. The use of visceral treatment for pain is complementary and is relevant for pregnant women. Maintaining the mobility and motility of internal organs by means of visceral techniques can regulate anatomical relations and physiological processes within the urogenital diaphragm. The role of physical activity is also important. A scoping review was conducted to analyze the relevant literature on pain in pregnant women, the role of visceral therapy in pregnant women and oxidative stress. Eligible articles presented aspects of the occurrence of pain in locomotive organs in pregnant women, the use of visceral therapy in pain management, and the reduction of oxidative stress. The use of visceral therapy and physical activity in the treatment of pain is complementary and also important for pregnant women, and so may have an effect on reducing oxidative stress in pregnant women.